2007
DOI: 10.1002/ccd.21400
|View full text |Cite
|
Sign up to set email alerts
|

Comparative rheology of low‐ and iso‐osmolarity contrast agents at different temperatures

Abstract: Background: Several contrast media (CM) are used for diagnostic angiography and coronary percutaneous interventions. Catheter miniaturization allows performance of most diagnostic studies using 4-5 F catheters and interventions using 5-6 F catheters. As a result of catheter lumen downsizing and viscosity of CM, the operators are sometimes required to forcefully inject to produce adequate images. Methods and Results: The aim of the study is to perform a comparative rheology analysis between three different comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Extrinsic warming of iodinated contrast material to 37°C reduces contrast material viscosity and has been advocated to decrease the frequency of adverse events related to intravenous administration (1)(2)(3)6,11,12 ) and to improve iodinated contrast material delivery ( 4,5 ). However, studies demonstrating effi cacy of a reduction in adverse risk from contrast material warming are scant, and the magnitude of demonstrable effect (when able to be shown at all [ 7 ]) has been small ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extrinsic warming of iodinated contrast material to 37°C reduces contrast material viscosity and has been advocated to decrease the frequency of adverse events related to intravenous administration (1)(2)(3)6,11,12 ) and to improve iodinated contrast material delivery ( 4,5 ). However, studies demonstrating effi cacy of a reduction in adverse risk from contrast material warming are scant, and the magnitude of demonstrable effect (when able to be shown at all [ 7 ]) has been small ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing proportion of procedures are being performed with 4 and 5 French diagnostic catheters, and radial percutaneous coronary interventions with guides as small as 4 French have been described . Brunette et al reported that significantly higher pressure was required for iodixanol to maintain similar catheter flow rates with ioxaglate at room temperature for adequate angiography. Coronary balloons are potentially more susceptible to the effects of high viscosity because of long catheter lengths and small lumen size.…”
Section: Discussionmentioning
confidence: 99%
“…It is questionable whether the high viscosity should be considered to be a disadvantage when comparing the various ICM. Viscosity also depends on temperature: heating the ICM to bring the temperature close to that of the body considerably reduces viscosity (Brunette et al, 2008).…”
Section: Contrast Media Osmolality To Reduce the Risk Of Contrast-indmentioning
confidence: 99%